Early stage reversed crystal growth of zeolite A and its phase transformation to sodalite - Greer, Heather; Wheatley, Paul S; Ashbrook, Sharon E; Morris, Russell E; Zhou, Wuzong (Journal of the American Chemical Society, 2009)
Microstructural analysis of the early stage crystal growth of zeolite A in hydrothermal synthetic conditions revealed a revised crystal growth route from surface to core in the presence of the biopolymer chitosan. The mechanism of this extraordinary crystal growth route is discussed. In the first stage, the precursor and biopolymer aggregated into amorphous spherical particles. Crystallization occurred on the surface of these spheres, forming the typical cubic morphology associated with zeolite A with a very thin crystalline cubic shell and an amorphous core. With a surface-to-core extension of crystallization, sodalite nanoplates were crystallized within the amorphous cores of these zeolite A cubes, most likely due to an increase of pressure. These sodalite nanoplates increased in size, breaking the cubic shells of zeolite A in the process, leading to the phase transformation from zeolite A to sodalite via an Ostwald ripening process. Characterization of specimens was performed using scanning electron microscopy and transmission electron microscopy, supported by other techniques including X-ray diffraction, solid-state NMR, and N(2) adsorption/desorption.